Developing Civic Literacy-Based Explosion Box to Enhance Pancasila Education Learning Outcomes - Muthia Resty; Reh Bungana Beru Perangin-angin; Yusnadi; Hapni Laila Siregar; Restu; Zuraida LBS (International Journal on Integrated Education, 2026)
Pancasila education is a crucial subject within the Merdeka Curriculum that requires creativity in delivering instructional materials to strengthen the civic literacy of primary school students. This study serves as a development research project for an innovative instructional medium specifically designed to support the active learning process for fifth-grade students at SD Negeri 132410 Tanjungbalai. The study aims to produce a civic literacy-based Explosion Box learning medium on the topic of "Norms in My Life" that meets the criteria of validity, practicality, and effectiveness. This research employed the Research and Development (R&D) method using the 4-D development model, consisting of the Define, Design, Develop, and Disseminate stages. The findings indicate that the medium was deemed highly valid based on validation by material experts (91%), media experts (90%), and linguists (88.6%). Practicality tests by teachers achieved 93.4%, while students' assessments reached 90%, both categorized as highly practical. Furthermore, the medium proved effective, with average pre-test scores increasing from 48.00 to 82.68 in the post-test, resulting in an N-Gain score of 68.47% (sufficiently effective). Hypothesis testing revealed a significance value of 0.000 < 0.05, confirming a significant difference in learning outcomes between the experimental and control classes. Consequently, the developed Explosion Box medium is proven to be valid, practical, and effective in enhancing student learning outcomes.